The OPERA trial: protocol for a randomised trial of an exercise intervention for older people in residential and nursing accommodation. - Underwood, M; Eldridge, S; Lamb, S; Potter, R; Sheehan, B; Slowther, A; Taylor, S; Thorogood, M; Weich, S (2011)
BACKGROUND: Depression is common in residents of Residential and Nursing homes (RNHs). It is usually undetected and often undertreated. Depression is associated with poor outcomes including increased morbidity and mortality. Exercise has potential to improve depression, and has been shown in existing trials to improve outcomes among younger and older people. Existing evidence comes from trials that are short, underpowered and not from RNH settings. The aim of the OPERA trial is to establish whether exercise is effective in reducing the prevalence of depression among older RNH residents. METHOD: OPERA is a cluster randomised controlled trial. RNHs are randomised to one of two groups with interventions lasting 12 months. INTERVENTION GROUP: a depression awareness and physical activity training session for care home staff, plus a whole home physical activation programme including twice weekly physiotherapist-led exercise groups. The intervention lasts for one year from randomisation, or CONTROL GROUP: a depression awareness training session for care home staff.Participants are people aged 65 or over who are free of severe cognitive impairment and willing to participate in the study. Our primary outcome is the prevalence of depressive symptoms, a GDS-15 score of five or more, in all participants at the end of the one year intervention period. Our secondary depression outcomes include remission of depressive symptoms and change in GDS-15 scores in those with depressive symptoms prior to randomisation. Other secondary outcomes include, fear of falling, mobility, fractures, pain, cognition, costs and health related quality of life. We aimed to randomise 77 RNHs. DISCUSSION: Home recruitment was completed in May 2010; 78 homes have been randomised. Follow up will finish in May 2011 and results will be available late 2011. TRIAL REGISTRATION: [ISRCTN: ISRCTN43769277].